Pengembangan Metode Bandongan dalam Kajian Kitab Kuning di Pesantren Attarbiyah Guluk-Guluk dalam Perspektif Muhammad Abid al-Jabiri - Effendi Chairi (Program Studi Manajemen Pendidikan Islam Institut Pesantren KH Abdul Chalim Mojokerto, 2019)
This article discusses one of development step of bandongan method applied at Pesantren Attarbiyah in Madura. In actual fact, author analyzed it by using contemporary of philosophical approach to find out the methodological basis in carrying out development and to fine out its success. In this case, author used Abid al-Jabiri’s thought of turats as a main approach in making observations. But author also used other approaches to analyze other main object within it, such as Paulo Friere’s thought used to analyze bandongan method and taxonomy’s Bloom used to analyze the success of it. This article presents the interesting research result that the development of bandongan method at Pesantren Attarbiyah can be mentioned successful because of several reasons. The first is continuity between tradition and modernity and it is synchronic with Abid al-Jabiri’s thought and the ushul-fiqh’s principle—al-muhafadzatu ‘ala qadim al-shalih, wa al-ahdzu bi al-jadid al-ashlah. Secondly, there is discussion season between santri that formerly had never happened for this method is monologue, teacher-centered, and indoctrination. On the other hand, this also can be mentioned a failure, although it is not entirely, because the understanding of santri is not the result of their critical thinking independence. But it is created by kiai.